PERAN PENYULUH PERTANIAN MELALUI ADOPSI TEKNOLOGI DAN FAKTOR-FAKTOR PRODUKSI USAHATANI PADI SAWAH DI DESA LAMOERI KECAMATAN ANGATA KABUPATEN KONAWE SELATAN - Hefbron Hefbron; Usman Rianse; Sukmawati Abdullah; Darsilan Dima (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The objective of this study is to determine the impact of agricultural extension workers on technology adoption and production factors in enhancing wet-rice farming in Lamoeri Village, Angata Subdistrict, South Konawe Regency. The study population consists of 180 registered rice paddy farmers who are members of 10 farmer groups affiliated with the Agricultural Extension Center (BPP). The study sample consisted of 36 individuals, which represents 20% of the population. The sampling method used was simple random sampling. Data was collected through interviews and documentation using questionnaires as instruments. The data was analyzed quantitatively using the class interval formula. The study found that agricultural extension officers in Lamoeri Village played a positive role in assisting rice paddy farmers. Their roles included facilitating, communicating, motivating, and consulting. The study also revealed that the adoption of innovations in rice paddy cultivation technology was generally successful. Extension workers have optimally carried out the stages of adoption of interest, evaluation, trial, and adoption. However, their role in the awareness stage needs improvement. The production process of paddy rice farming is influenced by natural factors, labor, facilities and infrastructure, and expertise factors. Therefore, it is crucial to always consider and prioritize these factors in order to increase farm productivity.